2013
DOI: 10.3892/br.2013.150
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of the Ginkgo biloba extract is associated with the enhancement of cytochrome P450 1B1 expression in estrogen receptor-negative breast cancer cells

Abstract: Abstract. Ginkgo biloba is a dioecious tree and its extract is a complex mixture that has been used for thousands of years to treat a variety of ailments in traditional Chinese medicine. The aim of this study was to present our observations on the inhibitory effects of different Ginkgo biloba extracts on human breast cancer cell proliferation and growth. Our results demonstrated that treatment of MCF-7 and MDA-MB-231 human breast cancer cells with Ginkgo biloba leaves and ginkgo fruit extract inhibited cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, no studies have provided conclusive mechanisms of action regarding the effects of GA C13:0 in human MCF-7 and mouse 4T-1 breast cancer cells. In our previous study, the fruit of GB extract showed inhibited proliferation in MCF-7 and MDA-MB-231 breast cancer cells and that accompanied by the enhancement of CYP1B1 mRNA expression [22]. In this study, we isolated GA C13:0 from the GBE and investigated the anti-proliferation, pro-apoptosis and anti-migration effects as well as the possible pivotal regulatory role of CYP1B1 in breast cancer cells.…”
Section: Introductionmentioning
confidence: 88%
“…However, no studies have provided conclusive mechanisms of action regarding the effects of GA C13:0 in human MCF-7 and mouse 4T-1 breast cancer cells. In our previous study, the fruit of GB extract showed inhibited proliferation in MCF-7 and MDA-MB-231 breast cancer cells and that accompanied by the enhancement of CYP1B1 mRNA expression [22]. In this study, we isolated GA C13:0 from the GBE and investigated the anti-proliferation, pro-apoptosis and anti-migration effects as well as the possible pivotal regulatory role of CYP1B1 in breast cancer cells.…”
Section: Introductionmentioning
confidence: 88%
“…Shi et al [ 39 ] examined the effects of EGb 761 on platelets and hippocampal mitochondria isolated from SMAP8 mice of different age groups. SMAP8 mice were a senescence-accelerated strain of mice.…”
Section: Pharmacological Actions Of Egbmentioning
confidence: 99%
“…EGb is also involved in several other cancers including breast cancer, non-small cell lung cancer (NSCLC), colon cancer and prostate cancer. Zhao et al [ 39 ] reported that GEb treatment could increase the expression of cytochrome P450(CYP)1B1 in MDA-MB-231 human breast cancer cells. Park et al [ 103 ] also found that EGb mediated cytotoxic effects in the breast cancer cell line MDA-MB-231 by activating caspase-3 and altering the mRNA levels of apoptosis-related genes Bcl-2 and Bax.…”
Section: The Effect Of Egb On Aging-related Diseasesmentioning
confidence: 99%
“…EGB is well known for its antioxidant and antiinflammatory activities (Ren et al, 2013). Previous studies showed that EGB may have antitumor effects that are related to its antioxidant, antiangiogenic, and gene-regulatory actions (Dias et al, 2013;Park et al, 2013;Zhao et al, 2013). Flavonoids and terpenoids are major biologically active components of EGB.…”
Section: Introductionmentioning
confidence: 99%